Analisis Implementasi Pembelajaran Bilingual di Sekolah Dasar Ditinjau dari Model, Pendekatan, Metode, dan Media - Agustina, Melda Dwi; Febriani, Rezza Sari; Rahmawati, Juninta Natasya; Ivenne L. N, Shyabila; Susanti, Putri Anisa; Situmeang, Widia Aprilia; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the implementation of bilingual learning in Elementary Schools in terms of models, approaches, methods, and learning media. The reason for choosing this topic is based on the importance of mastering two languages from an early age and the need to map out the right learning strategy. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observations of bilingual learning videos uploaded on YouTube, to describe how teachers plan and implement bilingual learning in real terms. The results of the study show that the preview-review model is effective in balancing the use of Indonesian and English. The communicative approach has been proven to develop students' language skills holistically. The Problem Based Learning method increases student participation and critical thinking, while media such as learning videos and teaching aids help deliver material contextually and interestingly. So the integration between the right models, approaches, methods, and media is very important to create interactive, meaningful bilingual learning that is able to develop the multilingual competence of elementary school students.